Pidana Mati dalam Perspektif Undang-Undang Nomor 1 Tahun 2023: Tinjauan Yuridis terhadap Model Pemidanaan Alternatif - Khusnul Baiti, Aqmarina (LPPM Universitas Harapan Bangsa, 2024)
Law Number 1 of 2023 concerning the Indonesian Criminal Code repositions the death penalty from an absolute sanction to a conditional alternative sentence, allowing a probationary period of ten years. This change reflects a paradigm shift from a retributive approach to a more humanistic model that emphasizes the protection of human rights, particularly the right to life, and incorporates the principles of proportionality, individualization, and ultimum remedium in criminal law. This research employs a normative juridical method using statutory and conceptual approaches, along with qualitative analysis of Articles 100 and 101 of the Criminal Code. The findings indicate that the conditional death penalty aligns with the principles of modern criminal law and constitutional values; however, its implementation faces significant normative and institutional challenges. Clear implementing regulations, evaluation standards, and judicial guidelines are required to ensure consistent application of the law. The readiness of law enforcement personnel, inter-agency coordination, and objective evaluation mechanisms are key prerequisites. The conditional death penalty has the potential to strengthen Indonesia’s criminal justice system in line with substantive justice and constitutional protection.